2013
DOI: 10.1007/s00415-013-7013-0
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral haemorrhage in a population-based stroke registry (LuSSt): incidence, aetiology, functional outcome and mortality

Abstract: Data on incidence of intracerebral haemorrhage (ICH) vary widely. Population-based data on predictors of ICH survival and functional outcome are rare. The Ludwigshafen Stroke Study is a prospective, population-based stroke registry which started in January 2006. All residents of the city of Ludwigshafen, Germany, who suffer from acute stroke or transient ischaemic attack are registered. Patients with first-ever primary intracerebral haemorrhage (FE-pICH) between 2006 and 2010 were included in the present analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
60
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 37 publications
4
60
2
3
Order By: Relevance
“…Our study has some limitations. First, the initial stroke severity and average admission NIHSS scores in our study were similar to previous reports by the Taiwan and Ludwigshafen Stroke Registries [37,38]. However, the overall mortality in our study was lower than other reports [38,39].…”
Section: Discussionsupporting
confidence: 89%
“…Our study has some limitations. First, the initial stroke severity and average admission NIHSS scores in our study were similar to previous reports by the Taiwan and Ludwigshafen Stroke Registries [37,38]. However, the overall mortality in our study was lower than other reports [38,39].…”
Section: Discussionsupporting
confidence: 89%
“…Lobar ICH has been associated with a better outcome in a population-based study, 11 but not in others, 14,17,18 which may be because of confounding. We found that lobar ICH location influenced survival and risk of recurrent ICH, independent of other known prognostic factors.…”
Section: Discussionmentioning
confidence: 79%
“…8,9 However, most ICHs are supratentorial and the influence of supratentorial ICH location on outcome remains unclear. Lobar ICH may have a better prognosis in comparison with ICH in other locations, [10][11][12][13] or it may not, [14][15][16][17][18][19][20] and the risk of recurrence may be higher after lobar ICH. 21 Determining whether risk factors and outcome differ according to ICH location has been further complicated by studies' varied definitions of ICH location.…”
mentioning
confidence: 99%
“…5, 14 In this cohort the mortality risk is similar to −Neuro-ICU studies 1, 2, 19, 20 and the distribution of good functional outcome similar to population based studies in Europe. 23, 24 A reduction in 90 day mortality of 29% was associated with transfer and varied in sensitivity analysis based on literature review. 1, 2, 5, 19, 20 …”
Section: Methodsmentioning
confidence: 99%